PARE0012 How to develop an independent youth organisation? risks, challenges and benefits. (23rd January 2014) - Van Nieuwkoop, L.; Poot, S.; Sauer, R.; van Nieuwkoop, C.; van der Geest, L.
Abstract : Background: Youth-R-Well.com is the national youth organisation in the Netherlands for young people with arthritis. They already exists for 8 years and started as a project of the national umbrella organisation for people with arthritis, Reumapatiëntenbond. Factors of success for Youth-R-Well.com are: It has always been a network for, by and with young people with arthritis; A strict age limit between 16 and 30; Online platform and Challenging events. Because of the liquidation of Reumapatiëntenbond, the only way to continue these activities was to become an independent organisation, which we are since 2012. In becoming an independent organisation for young people with arthritis the organisation faces risks and challenges, but there are also benefits. Results: Benefits of an independent youth organisation: Self-determination by young people themselves; Absence of any pressure to conform to the policy and house style of the mother organisation; Absence of conflict of interest: Develop own policy, practices and membership form. Independence from a mother organisation guarantees that the interests of young people with arthritis are really in the centre. We focus solely on the needs and expectations of younger people; Limited overhead costs. Risks and disadvantages of independence: As a consequence of working only with volunteers, it is difficult to maintain continuity. The boardmembers have many responsibilities which is not always feasible. Apart from the voluntary work, most study or have a job. Voluntary work needs to be fun, which cannot always be offered. As a consequence the voluntary work is often experienced as without any obligation;No opportunity to become a member of the PARE-network;Lack of monitoring over the organisation;Reduced opportunities for collaboration with other organisations when there is no umbrella or mother organisation. This might lead to the risk of duplicating activities, lack of synergy, miscommunications and loss of power as a consequence of disintegration instead of joining forces. Challenges: Taking responsibility;Organizing logistics: We have no office, no phone number, no helpline. The online community should provide full service to the members of our network;Establishment and sustainability of the youth network;Policy for voluntary work: How do we keep the work fun and enjoyable, without getting lost in burocracy which seems to be intrinsic to the governance of an organisation;To stay active and involved on an international level without becoming an official member of PARE;How to develop and create knowledge and skills that are necessary to maintain a lively and professional organisation?;Raising funds to make activities financially possibly and hopefully in the future the possibility to have an employee (which will take away some of the risks there are working only with volunteers). Conclusions: Starting as a project of Reumapatiëntenbond made it possible to establish Youth-R-Well.com. During the first 8 years the basis of collaboration with other organisation was laid and a network was build. The greatest challenge now is continuing the activities. The reason why Youth-R-Well.com made it this far is because of the hard work of the active boardmembers led by intrinsic motivation. The lack of a national umbrella patient organisation makes good collaboration more difficult. Disclosure of Interest: None Declared